2009
DOI: 10.1121/1.3206583
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of models for diotic and dichotic detection in reproducible noises

Abstract: Several psychophysical models for masked detection were evaluated using reproducible noises. The data were hit and false-alarm rates from three psychophysical studies of detection of 500-Hz tones in reproducible noise under diotic ͑N 0 S 0 ͒ and dichotic ͑N 0 S ͒ conditions with four stimulus bandwidths ͑50, 100, 115, and 2900 Hz͒. Diotic data were best predicted by an energy-based multiple-detector model that linearly combined stimulus energies at the outputs of several critical-band filters. The tone-plus-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 36 publications
4
47
0
Order By: Relevance
“…More recently, Goupell and Hartmann (2007) proposed "independent-center" and "auditory-image" models that linearly combined ILDs and ITDs to predict listeners' performance for interaural correlation detection; the difference between these two models was the sequence of combining ILD and ITD information and integrating across time. Predictions from Goupell and Hartmann's models were significantly correlated with detection patterns for about half of the listeners (Davidson et al, 2009a). However, Davidson et al (2009a) found by examining data from each listener that either ILDs or ITDs dominated in Goupell and Hartmann's linear combinations, suggesting that instead of combining ILDs and ITDs, in fact only the better of the two cues was used by the models.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…More recently, Goupell and Hartmann (2007) proposed "independent-center" and "auditory-image" models that linearly combined ILDs and ITDs to predict listeners' performance for interaural correlation detection; the difference between these two models was the sequence of combining ILD and ITD information and integrating across time. Predictions from Goupell and Hartmann's models were significantly correlated with detection patterns for about half of the listeners (Davidson et al, 2009a). However, Davidson et al (2009a) found by examining data from each listener that either ILDs or ITDs dominated in Goupell and Hartmann's linear combinations, suggesting that instead of combining ILDs and ITDs, in fact only the better of the two cues was used by the models.…”
Section: Introductionmentioning
confidence: 87%
“…Predictions from Goupell and Hartmann's models were significantly correlated with detection patterns for about half of the listeners (Davidson et al, 2009a). However, Davidson et al (2009a) found by examining data from each listener that either ILDs or ITDs dominated in Goupell and Hartmann's linear combinations, suggesting that instead of combining ILDs and ITDs, in fact only the better of the two cues was used by the models.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The fluctuations in the ILD, s t ðDLÞ, were calculated similarly by using the ILDs in the instantaneous envelope of the analytic signal. These two statistics have been used in several studies to account for binaural detection sensitivity (e.g., Goupell and Hartmann, 2007;Davidson et al, 2009;van der Heijden and Joris, 2009). …”
Section: Fluctuations In Interaural Differencesmentioning
confidence: 99%